PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN MODEL PEMBELAJARAN CONCEPT SENTENCE PADA SISWA SEKOLAH DASAR - Islami, Rahma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The type of research is Classroom Action Research (CAR) using a qualitative approach. This research is the subject Elementary School fifth grade students of District 09 Feed Sinayan Banuhampu many as 20 students. The study consisted of 2 cycles. The design of this study include (1) planning, (2) implementation, (3) observations, (4) Reflection. Results of research carried out every cycle has increased narrative essay writing skills. Average mastery of student learning outcomes in the first cycle of 68.2% prewriting stage, the stage of writing 69%, and 73.8% pascapenulisan stage, there was an increase in the second cycle is the prewriting stage of 78.2%, 77.1% stage writing , and 80.4% pascapenulisan stage.   Kata Kunci : keterampilan, menulis karangan, concept sentence